Rescue of cardiac α-actin-deficient mice by enteric smooth muscle γ-actin - Kumar, A. (The National Academy of Sciences of the USA, 1997)
The muscle actins in higher vertebrates display highly conserved amino acid sequences, yet they show distinct expression patterns. Thus, cardiac α-actin, skeletal α-actin, vascular smooth muscle α-actin, and enteric smooth muscle γ-actin comprise the major actins in their respective tissues. To assess the functional and developmental significance of cardiac α-actin, the murine (129/SvJ) cardiac α-actin gene was disrupted by homologous recombination. The majority (≈56%) of the mice lacking cardiac α-actin do not survive to term, and the remainder generally die within 2 weeks of birth. Increased expression of vascular smooth muscle and skeletal α-actins is observed in the hearts of newborn homozygous mutants and also heterozygotes but apparently is insufficient to maintain myofibrillar integrity in the homozygous mutants. Mice lacking cardiac α-actin can be rescued to adulthood by the ectopic expression of enteric smooth muscle γ-actin using the cardiac α-myosin heavy chain promoter. However, the hearts of such rescued cardiac α-actin-deficient mice are extremely hypodynamic, considerably enlarged, and hypertrophied. Furthermore, the transgenically expressed enteric smooth muscle γ-actin reduces cardiac contractility in wild-type and heterozygous mice. These results demonstrate that alterations in actin composition in the fetal and adult heart are associated with severe structural and functional perturbations.